Bogota’s theaters as type and image of the city in 1970 and 2010 (2010)
Beginning from the notion of type as proposed by Aldo Rossi in 1971 and taking Bogota’s theaters as field of study, the article examines how this concept can actually be applied tocertain body of phenomena inasmuch as how the evolution of the city is engraved in those constructions. It also analyzes whether or not such cinemas could be considered as types, then it provides us with some reasons as to why public attendance shortened so suddenly, and finally it presents a complete account of the theaters functioning by the 1970s and theiractual condition as well. As a conclusion, it defines the percentage of those cinemas that currently preserve their façade and maintain their exterior appearance, those that have been recycled, their building-use changed, remodeled to reopen theirdoors as projection screens or other cultural purposes, and those that have been sadly demolished.